Policy Brief: Is There a New Track Two? Taking Stock of Unofficial Diplomacy in Peacemaking - Palmiano Federer, Julia (Université d'Ottawa | University of Ottawa, 2021)
Ottawa Dialogue's First Policy Brief by Dr Julia Palmiano Federer looks at the evolution of Track Two since it was first named in the early 1980s. Based on academic and policy scholarship on Track Two and her research on NGO mediators, Dr Palmiano Federer identifies the key ideas and concepts which have shaped the discussion of the field in this time and provides insight into where Track Two may be going.
Keywords: Track Two Diplomacy; Mediation; Peacebuilding; Diplomacy